Kajian Intertekstualitas Penokohan Rahwana Dalam Novel Rahvayana Karya Sujiwo Tejo Dan Implementasinya Sebagai Bahan Ajar Sastra Di Smp Negeri 2 Matesih - Kusdiwanto, Arif; , Dra. Main Sufanti, M.Hum (2017)
The purpose of this study was to describe (1) the structure of the building novel Rahvayana by Sujiwo Tejo includes characterization, theme, plot, setting, and viewing angle; (2) intertextual characterizations figures Rahwana in the novel Rahvayana by Sujiwo Tejo; (3) the implementation of the research results as teaching materials in junior high literature. In connection with the research objectives, form study is a qualitative research. The object of this study is intertextuality dispositive character Rahwana in the novel Rahvayana Sujiwo work Tejo. Sources of data in this study is novel Rahvayana by Sujiwo Tejo. The data collection technique used is the technique of the literature, see, and record. Validation of data used triangulation theory and triangulation data. Data analysis technique used is the intertextual and heuristic models and herneneutik readings. The results of this study are: (1) the structure of the novel Rahvayana includes (1) characterization, (2) theme, (3) plot, (4) setting, and (5) viewing angle; (2)judging from the structure, Rahvayana own characterizations Rahwana and Sinta as the main character ; themes: love and heroic; fidelity advanced groove; background are Borobudur, Bali, Dubai, and Berlin ; and viewpoint: viewpoint of first person perpective (3) Rahvayana novel form of intertextuality in this study is the rejection and the inaugural convention ;(4) the results of this study can be implemented as a literary teaching materials into teaching literature in class IX SMP SMP ie 2nd semester (even) in accordance with the Education Unit Level Curriculum (SBC).